2021
DOI: 10.1155/2021/5530293
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction Contributes to Aging‐Related Atrial Fibrillation

Abstract: The incidence of atrial fibrillation (AF) increases with age, and telomere length gradually shortens with age. However, whether telomere length is related to AF is still inconclusive, and the exact mechanism by which aging causes the increased incidence of AF is still unclear. We hypothesize that telomere length is correlated with aging-related AF and that mitochondrial dysfunction plays a role in this. This research recruited 96 elderly male patients with AF who were admitted to the Second Medical Center of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Mitochondrial dysfunction contributes significantly to aging-related diseases (216)(217)(218). However, treatment with quercetin could reduce ROS generation and mitigate mitochondrial dysfunction, thereby maintaining the mitochondrial homeostasis and normal function.…”
Section: Quercetin Regulates Mitochondrial Function Via Sirt1mentioning
confidence: 99%
“…Mitochondrial dysfunction contributes significantly to aging-related diseases (216)(217)(218). However, treatment with quercetin could reduce ROS generation and mitigate mitochondrial dysfunction, thereby maintaining the mitochondrial homeostasis and normal function.…”
Section: Quercetin Regulates Mitochondrial Function Via Sirt1mentioning
confidence: 99%
“…Mitochondrial dysfunction and systemic inflammation may bridge the gap between NAFLD and AF. Literature and our previous study found that mitochondrial dysfunction is involved in the pathogenesis of NAFLD and AF ( Chen et al, 2021 ; Liu et al, 2021 ). Under metabolic stress conditions, ROS production increases in mitochondria, and once ROS levels exceed the neutralization capacity of its own antioxidant system, it damages the mitochondrial membrane and mitochondrial DNA, causing mitochondrial dysfunction and inducing hepatic inflammation via the nuclear factor-κB (NF-κB) and nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP 3) pathways ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
“…When cardiomyocyte mitochondrial dysfunction occurs, ΔΨm decreases, ATP production decreases, leading to the opening of membrane ATP-sensitive potassium channels (sarcKATP), slowing of myocardial localized electrical activity conduction, increasing inhomogeneity, and ease of formation of refractoriness, which induces AF ( Lkhagva et al, 2021 ). In addition, myocardial mitochondria store a large amount of Ca2+, which is a reservoir of intracellular Ca2+, and when mitochondrial dysfunction occurs, the intracellular calcium balance is disturbed, which promotes the occurrence of AF ( Liu et al, 2021 ). It is believed that NAFLD potentially contribute to structural, functional, electrical, and autonomic remodeling of the heart by induce metabolic disorders, inflammation, oxidative stress and promote epicardial adipose tissue (EAT) expansion, which ultimately leading to increased susceptibility to AF ( Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether there is a relationship between LTL and AF is still controversial. Several cross-section studies have shown the positive link between LTL and the occurrence of AF that age-adjusted LTL decreased by 9% for subjects with a history of AF versus controls ( n = 3,576, p = 0.017) ( 8 , 9 ). Short-term cohort studies also indicate that shorter LTL was associated with the progression and recurrence of AF ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%